THE IMPACT OF ERP AND XBRL IMPLEMENTATION ON THE ACCOUNTING INFORMATION QUALITY - Lestari, Tri Utami; Musrady, Raihan Aqil Fauzananda (LPPM STIE Muhammadiah Bandung, 2023)
One of the indicators of the quality of accounting information is timeliness, which indicates that the information in the financial statements is usable. In Indonesia, the industrial development of the consumer cyclical sector tends to fluctuate in tandem with economic growth. The economic growth rate will increase by 5.05% between 2019 and 2021; Indonesia’s economy will grow by 3.69% in 2021, down from 2.07% in 2020. The Indonesia Stock Exchange and the Financial Services Authority have established rules regarding the submission of financial reports. Nonetheless, many companies in the consumer cyclical sector on the Indonesia Stock Exchange are still delinquent in submitting their financial reports. This study seeks to determine how enterprise resource planning and extensible business implementation reporting language affect the timeliness of financial report submissions. This study employs a quantitative research methodology. This study’s population consists of cyclical consumer sector firms listed on the Indonesia Stock Exchange between 2019 and 2021. This study employed a purposive sampling strategy to collect 115 research samples over a 3-year observation period for a total of 345 research samples. According to the study’s findings, enterprise resource planning and extensible business reporting language impact the timeliness of financial reporting simultaneously. Although partially, only the extensible business reporting language significantly impacts the timeliness of financial report submission. In the meantime, enterprise resource planning does not significantly impact the timeliness of financial report submission. In order to avoid sanctions from the Indonesia Stock Exchange and the Financial Services Authority, it is hoped that consumer cyclical sector companies listed on the Indonesia Stock Exchange will always adhere to the deadline for submitting financial reports to the public.